Comment une friche ferroviaire se transforme en quartier durable : Le quartier Écoparc à Neuchatel en Suisse - Federica Merzaghi; Malika Wyss (VertigO)
Fallow railway areas represent a significant building potential at the very city centers. In a context of increasing awareness of the environmental and social consequences of extensive urbanism, recycling such areas in view of new neighborhood building makes sense completely for the objective of limiting city expansion. This article gives an account of the conceptual, interactional and institutional mechanisms that underlying the construction and the implementation of a project aiming to transform a fallow railway area into a sustainable neighborhood. We will focus particularly on the complexity of this collective action and on the sequence of compromises it presupposes, both in its substantial and in its organizational aspects.